Eliciting medication preferences of patients with type 2 diabetes under different insurance coverages in China - Zheng, Lvyun; Liu, Shimeng; Liu, Zhigang; Cao, Chenchen; Xue, Wenjing; Chen, Yingyao; Liu, Jing (Frontiers in Public Health, 2024)
Objective To understand the medication preference of type 2 diabetes mellitus (T2DM) patients with different insurance coverages, and to provide reference for improving the patient-centered clinical treatment decision. Methods This study used Discrete Choice Experiment (DCE) to elicit preferences of T2DM patients with different insurance coverages in China. A multistage stratified cluster-sampling procedure for data collection and a total of 1,409 valid respondent were conducted. Results Seven attributes have significant influence on the preference of T2DM patients with Urban Employee Basic Medical Insurance (UEBMI) and Urban and Rural Residents Basic Medical Insurance (URRBMI) (p < 0.05). T2DM patients with UEBMI pay the most attention to Gastrointestinal adverse events, while T2DM patients with URRBMI pay the most attention to the Treatment efficacy/reduction in HbA1c. Patients with different medical insurance have different willingness to pay for Cardiovascular benefits, Mode of administration and Weight change. When Gastrointestinal adverse events is changed from higher (40%) to none (0%), patients with UEBMI are willing to pay ¥523.49 more per month, while patients with URRBMI are only willing to pay ¥266.62; When the Treatment efficacy/reduction in HbA1c changes from poor (0.5%) to Highest (2.5%), patients with UEBMI are willing to pay ¥518.44 more per month, while patients with URRBMI are willing to pay ¥328.33 more per month. The Gastrointestinal adverse events and the Treatment efficacy/reduction in HbA1c are the primary factors for T2DM patients with UEBMI and URRBMI, followed by the Hypoglycemic risk. Conclusion Physicians should consider patients’ medication preferences in clinical medication treatment of T2DM patients with different insurance coverages, make targeted treatment decisions, and improve patients’ medication compliance to achieve better treatment results.